2014
DOI: 10.1590/1516-3180.2014.1323568
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in inflammatory bowel disease: prevalence, differential diagnosis and association with clinical and laboratory variables

Abstract: CONTEXT AND OBJECTIVES: Anemia is the most frequent extraintestinal complication of inflammatory bowel disease. This study aimed to: 1) determine the prevalence of anemia among patients with inflammatory bowel disease; 2) investigate whether routine laboratory markers are useful for diagnosing anemia; and 3) evaluate whether any association exists between anemia and clinical/laboratory variables. DESIGN AND SETTING: Cross-sectional at a federal university. METHODS: 44 outpatients with Crohn's disease and 55 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…This finding is in accordance with an overall prevalence of anemia (24%, 95% CI, 18–31) found on a recent meta-analysis evaluating 2192 IBD patients in European countries [ 18 ]. Other studies reported similar prevalence between 17% and 20% [ 19 21 ] which differs from the higher prevalence of anemia found in the studies of Bergamisch et al [ 13 ] (65%) and Høivik et al [ 4 ] (48.8% on CD and 20.2% on UC). This probably is due to the fact that our study was conducted in patients who were already under IBD treatment while the latter two studies evaluated patients before starting treatment.…”
Section: Discussionmentioning
confidence: 52%
“…This finding is in accordance with an overall prevalence of anemia (24%, 95% CI, 18–31) found on a recent meta-analysis evaluating 2192 IBD patients in European countries [ 18 ]. Other studies reported similar prevalence between 17% and 20% [ 19 21 ] which differs from the higher prevalence of anemia found in the studies of Bergamisch et al [ 13 ] (65%) and Høivik et al [ 4 ] (48.8% on CD and 20.2% on UC). This probably is due to the fact that our study was conducted in patients who were already under IBD treatment while the latter two studies evaluated patients before starting treatment.…”
Section: Discussionmentioning
confidence: 52%
“…Iron deficiency is the most frequent cause of anemia in IBD patients, like in healthy people, with prevalence estimated in 36–90% [17]. It was demonstrated that iron deficiency has multifactorial etiology, including inadequate intake, blood loss from damaged intestinal wall, impairment absorption (disease localization in duodenum or proximal tract of jejunum), and impairment utilization (due to the systemic inflammatory status) [18, 19]. Furthermore, iron absorption and metabolism are regulated by Hepcidin and soluble transferrin receptors, the first being an important hormone depressing iron absorption and iron release from body stores in iron-overload and in inflammatory status; the second, conversely, increases during iron deficiency status and increases intestinal absorption and release from stores.…”
Section: Clinical Aspects Of Malnutrition In Patients With Ibdmentioning
confidence: 99%
“…Better parameters to identify iron deficiency such as soluble transferrin receptor (sTfR) are not applied widely ( 26 ). If the “traditional” markers appeared to be in a normal range and there still was an anemic blood count in IBD patients, this was attributed to “anemia of chronic disease” ( 24 , 27 29 ). Consecutively, this was a diagnosis of exclusion and no positive criteria were used.…”
Section: Iron Deficiency In Ibd Patientsmentioning
confidence: 99%